Sr, Nd, Pb and Os isotope systematics of CAMP tholeiites from Eastern North America (ENA): Evidence of a subduction-enriched mantle source - Merle, Renaud; Marzoli, A.; Reisberg, L.; Bertrand, H.; Nemchin, Alexander; Chiaradia, M.; Callegaro, S.; Jourdan, Fred; Bellieni, G.; Kontak, D.; Puffer, J.; Gregory McHone, J. (2014)
The Central Atlantic Magmatic Province (CAMP) is one of the largest igneous provinces on Earth, with an areal extent exceeding 107km2. Here we document the geochemical characteristics of CAMP basalts fromTriassic-Jurassic basins in northeastern USA and Nova Scotia (Canada).The CAMP rocks occur as lava flows, sills and dykes. All of our analysed samples show chemical characteristics typical of CAMP basalts with low titanium content, which include enrichment in the most incompatible elements and negative Nb anomalies. All the basalts also show enriched Sr-Nd-Pb initial (t=201Ma) isotopic compositions (206Pb/204Pbini.=18·155-18·691, 207Pb/204Pbini.=15·616-15·668, 208Pb/204Pbini.= 38·160-38·616, 143Nd/144Ndini.=0·512169-0·512499). On the basis of stratigraphy, rare earth element (REE) chemistry and Sr- Nd-Pb isotope composition, three chemical groups are defined. The Hook Mountain group, with the lowest La/Yb ratios, initial 206Pb/204Pbini.>18·5 and 143Nd/144Ndini>0·51238, comprises all the lastest and upper stratigraphic units. The Preakness group, with intermediate La/Yb ratios, 206Pb/204Pbini.>18·5 and 0·512334143Nd/144Ndini>0·51225, comprises the intermediate units. The Orange Mountain group has the highest La/Yb ratios and 143Nd/144Ndini.<0·51235 and involves all the earliest and stratigraphically lowest units, including the entire North Mountain basalts from Nova Scotia. In this last group, three sub-groups may be distinguished: the Rapidan sill, which has 206Pb/204Pbini. higher than 18·5, the Shelburne sub-group, which has 143Nd/144Ndini.<0·51225, and the remaining Orange Mt samples. With the exception of one sample, the Eastern North America (ENA) CAMP basalts display initial 187Os/188Os ratios in the range of mantle-derived magmas (<0·15). Simple modelling shows that the composition of the ENA CAMP basalts cannot plausibly be explained solely by crustal contamination of oceanic island basalt (OIB), mid-ocean ridge basalt (MORB) or oceanic plateau basalt (OPB) magmas. Mixing of such magma compositions with subcontinental lithospheric mantle (SCLM)-derived melts followed by crustal contamination, by either assimilation-fractional crystallization (AFC) or assimilation through turbulent ascent (ATA) processes is somewhat more successful. However, this latter scenario does not reproduce the REE and isotopic composition of the ENA CAMP in a fully satisfactory manner. Alternatively, we propose a model in which asthenospheric mantle overlying a subducted slab (i.e. mantle wedge) was enriched during Cambrian to Devonian subduction by sedimentary material, isotopically equivalent to Proterozoic-Lower Paleozoic crustal rocks. Subsequently, after subduction ceased, the isotopic composition of this mantle evolved by radioactive decay for another 170Myr until the CAMP magmatic event. Varying amounts and compositions of the incorporated sedimentary component coupled with radiogenic ingrowth over time can account for the main geochemical characteristics of the ENA CAMP (enriched incompatible element patterns, negative Nb anomalies, enriched Sr-Nd-Pb isotopic composition) and the differences between the three chemical groups. © The Author 2013. Published by Oxford University Press. All rights reserved.